Decolonizing nature : contemporary art and the politics of ecology - Demos, T. J. (Berlin : Sternberg Press, 2016)
While ecology has received little systematic attention within art history, its visibility and significance has grown in relation to the threats of climate change and environmental destruction. By engaging artists? widespread aesthetic and political engagement with environmental conditions and processes around the globe?and looking at cutting-edge theoretical, political, and cultural developments in the Global South and North?Decolonizing Nature offers a significant, original contribution to the intersecting fields of art history, ecology, visual culture, geography, and environmental politics. Art historian T. J. Demos, author of Return to the Postcolony: Specters of Colonialism in Contemporary Art (2013), considers the creative proposals of artists and activists for ways of life that bring together ecological sustainability, climate justice, and radical democracy, at a time when such creative proposals are urgently needed.
Introduction -- The art and politics of sustainability -- Climates of displacement from the Maldives to the Arctic -- The post-natural condition: art after nature? -- ¡Ya basta! : Ecologies of art and revolution in Mexico -- Nature's sovereignty : conflicting environments of development in India -- Decolonizing nature : making the world matter -- Gardening against the Apocalypse : the case of dOCUMENTA (13) -- Ways forward.
boek